Molecular Toxicology and Cancer Prevention - Sun, Guohui; Wang, Chongwen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Molecular toxicology is a field that investigates the interactions between chemical or biological molecules and organisms at the molecular level. In this Special Issue, we focus on the toxic effects and mechanisms of action of chemical and biological molecules, will be of great interest of readers in molecular toxicology and applied pharmacology.